Towards a Biopolitics of the People. From Arendt to Agamben and Back Again - Pistrol, Florian; Mayerhofer, Melanie (HannahArendt.net, 2022)
Among the many reactions from philosophers and political theorists to the coronavirus crisis, Giorgio Agamben’s is the most extreme. According to the Italian philosopher, governments all over Europe use Covid-19 as a pretext to end Western democracy. The measures they have taken are meant not so much to slow down the spread of the virus as to render the citizenry politically powerless by reducing them to their sheer biological existence. This interpretation of the pandemic and its political aftermath builds on the notion of biopolitics that Agamben advances in his multi-volume Homo Sacer series. And this notion, in turn, owes a great deal to the thought of Hannah Arendt. This leaves one pondering whether Agamben’s is the only way to avail oneself of Arendt’s ideas in order to tackle the coronavirus crisis. This paper responds to this question with a resounding no. It shows that Arendt’s thought can be put to quite different use. Rejecting Agamben’s vision of doom, we hold that the Covid-19 pandemic calls for an Arendtian conception of biopolitics that centres not on fatalism but on agency. The structure of this paper is as follows. First, we defend the proposition that what Agamben calls biopolitics is but a generalization of Arendt’s account of totalitarian domination. Second, we offer a critique of Agamben’s take on the coronavirus crisis, which bears alarming similarities to right-wing conspiracy theories. Third, we bring into relief Arendt’s keen awareness of the profound impact our active life has on the natural world. We combine this awareness with her definition of human beings as conditioned beings to suggest that she is mindful of the fact that our interacting with nature rebounds on us. This leads us to contend that Arendt, in a way, points us towards the unpleasant truth of Covid-19—namely, that it is the result of our foul treatment of the natural world. Fourth, we argue that since the way we affect nature is mediated by how we conduct our active life, the proper response to the coronavirus crisis is for us to change the latter, thus rendering it a matter of political concern. This politicization of our active life amounts to an Arendtian conception of biopolitics that is fundamentally different from Agamben’s. Where his take on biopolitics revolves around political impotence, ours concentrates on agency—on our ability, that is, to join together and make a new beginning.